Genomic Structure and Promoter Analysis of the Bubalus Bubalis Leptin Gene - Napolitano, Francesco (Journal of Buffalo Science, 2012)
The buffalo is an animal ever-growing in our hemisphere, one of the major problems for the genetic improvement of this species, concerns two reproductive aspects: the difficult heat detection and the seasonality of the oestrus cycles. The leptin plays a critical role in the regulation of reproductive and immune function in humans, it is at the centre of the complex networks that coordinate changes in nutritional state with many diverse aspects of mammalian biology. We have sequenced the 5’ flanking region and exon 1 of the leptin gene in buffalo. The sequencing is the ’first step’ for understanding the role of various parts of the genome and is a springboard from which to decode the genome. The simple sequencing, in fact, does not provide information directly applicable to understand the mechanisms underlying physiological and pathological processes, but represents a necessary step through which you can identify the role of different regions of DNA. However, waiting for the complete genome sequence of the buffalo, the database of the bovine genome offers the opportunity to investigate the buffalo genome in genes which are recognized to influence physiological processes related to reproduction in other species. In this context, our research had decided to investigate the leptin gene and particularly the regulatory area: the promoter.